PENGGUNAAN GOOGLE FORM SEBAGAI MEDIA EVALUASI PEMBELAJARAN PAI DI SEKOLAH MENENGAH ATAS NEGERI 1 BATANG ANAI - Armi Gusvita; Mahyudin Ritonga; Wedy Nasrul (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
Information and communication technology plays an important role in education, an educator is required to be able to integrate information and communication technology in defense of Jan. The evaluation model that took place during this time at SMA Negeri 1 Batang Anai is with conventional media such as the utilization of stationery. The concept of evaluation based on information and communication technology can be realized in the evaluation of daily learning in the classroom not just in national exams. In line with this research will describe the use of Google Form in pai learning evaluation activities at SMA Negeri 1 Batang Anai. To achieve these goals, in this study used qualitative methods with observation data collection techniques, interviews and documentation studies. The results found from the study show that the use of google form as an evaluation medium in islamic religious education learning at SMA Negeri 1 Batang Anai Got a positive response from teachers, because the creation of evaluation media with google form is more saving energy, cost and time and the inaccuracy of questions and evaluation results can be declared valid because in the application goole form there is already an analysis of the level of difficulty of the question and the results of the value of students in comparison with conventional media. Creating evaluation media using google form is easier and more fun because it can set the header design according to the teacher's wishes. While the response of students is fun, active and more interested in making students not afraid to follow the evaluation